2023
DOI: 10.3389/fimmu.2022.1089286
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intraocular anti-VEGF antibody treatment under in vitro HTLV-1 infection

Abstract: IntroductionHTLV-1 (human T-cell lymphotropic virus type 1) is a retrovirus that infects approximately 20 million people worldwide. Many diseases are caused by this virus, including HTLV-1–associated myelopathy, adult T-cell leukemia, and HTLV-1 uveitis. Intraocular anti–vascular endothelial growth factor (VEGF) antibody injection has been widely used in ophthalmology, and it is reportedly effective against age-related macular degeneration, complications of diabetic retinopathy, and retinal vein occlusions. HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…However, subsequent research has suggested Tax-independent secretion of VEGF 57 , 58 , and no significant differences were found in VEGF levels between HAM/TSP, ATLL, and healthy or asymptomatic carriers 59 , 60 . Furthermore, a recent study revealed a lack of efficacy of intraocular anti-VEGF antibody treatment on activated NF-κB, inflammatory cytokines/chemokines, and HTLV-1 proviral load 61 . The VEGF-A splice variant VEGF 165 is a ligand of the HTLV-1 receptor Neuropilin-1 (NRP-1), and HTLV-1 mimics VEGF 165 to recruit HSPGs and NRP-1 62 .…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent research has suggested Tax-independent secretion of VEGF 57 , 58 , and no significant differences were found in VEGF levels between HAM/TSP, ATLL, and healthy or asymptomatic carriers 59 , 60 . Furthermore, a recent study revealed a lack of efficacy of intraocular anti-VEGF antibody treatment on activated NF-κB, inflammatory cytokines/chemokines, and HTLV-1 proviral load 61 . The VEGF-A splice variant VEGF 165 is a ligand of the HTLV-1 receptor Neuropilin-1 (NRP-1), and HTLV-1 mimics VEGF 165 to recruit HSPGs and NRP-1 62 .…”
Section: Discussionmentioning
confidence: 99%